Working the phones: control and resistance in call centres - Woodcock, Jamie (London, 2017)
"Over a million people in the UK work in call centres, and the phrase has become synonymous with low-paid and high stress work, dictatorial supervisors and an enforced dearth of union organisation. However, rarely does the public have access to the true picture of what goes on in these institutions. For Working the Phones, Jamie Woodcock worked undercover in a call centre to gather insights into the everyday experiences of call centre workers. He shows how this work has become emblematic of the shift towards a post-industrial service economy, and all the issues that this produces, such as the destruction of a unionised work force, isolation and alienation, loss of agency and, ominously, the proliferation of surveillance and control which affects mental and physical wellbeing of the workers. By applying a sophisticated, radical analysis to a thoroughly international 21st century phenomenon, Working The Phones presents a window onto the methods of resistance that are developing on our office floors, and considers whether there is any hope left for the modern worker today."